2016
DOI: 10.1007/s00106-016-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomie und Physiologie der ableitenden Tränenwege

Abstract: Ophthalmologists and interventional radiologists are not the only professionals for whom diseases of the efferent tear duct system occupy centre stage; this applies also to ENT specialists involving endonasal conservative or surgical treatment. On the basis of current knowledge and taking account of results yielded by own research in recent years and of clinical aspects, we here give an overview of basic knowledge on the anatomy and physiology of the nasolacrimal system. In doing so functional aspects regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
0
11
0
6
Order By: Relevance
“…This suggests that the viral concentration and genome fraction is diverse in different sites. In consideration of the fact that the ocular surface is an open microenvironment, and that the viral may transport to the inferior meatus of the nose rapidly [14], the SARS-CoV-2 concentration in ocular surface is likely to be very low. We also found that suspected patients often had 2-3 repeated tests of nasopharyngeal swabs before the positive result confirmed SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…This suggests that the viral concentration and genome fraction is diverse in different sites. In consideration of the fact that the ocular surface is an open microenvironment, and that the viral may transport to the inferior meatus of the nose rapidly [14], the SARS-CoV-2 concentration in ocular surface is likely to be very low. We also found that suspected patients often had 2-3 repeated tests of nasopharyngeal swabs before the positive result confirmed SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…The nasolacrimal system provides a significant anatomical bridge between the ocular and respiratory systems. 52 Based on this bridge, tear fluid from the ocular surface is transported to the inferior meatus of the nose, which facilitates viral movement from the ocular surface to the respiratory tract. The ocular mucosal immune system and nasolacrimal ducts further share immunological interdependence.…”
Section: Link Between the Ocular And Respiratory Systemsmentioning
confidence: 99%
“…36 mm lang. In kraniokaudaler Richtung verlaufen die TNW leicht divergent zur Mittellinie und zeigen zudem in der anteroposterioren Projektion eine dorsale Auslenkung [1].…”
Section: Anatomische Und Physiologische Grundlagen Des Tränenabtranspunclassified
“…Die TNW-Schleimhaut verfügt ferner über ein eigenes lymphatisches Gewebe und ist reich an T-Lymphozyten. Hierüber kann die Antigenerkennung und nachfolgende Immunantwort moduliert werden [1].…”
Section: Merkeunclassified